ALLELOPATHIC EFFECTS AND INSECTICIDAL ACTIVITY OF Salvia sclarea L. - ŠUĆUR, Jovana; POPOVIĆ, Aleksandra; PETROVIĆ, Miloš; ANAČKOV, Goran; MALENČIĆ, Djordje; PRVULOVIĆ, Dejan (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Extensive use of synthetic pesticides has negative effects on the environment and on human and animal health. Knowledge of allelopathic interactions could provide powerful tools for a better exploitation of natural resources in the management of weeds and insects without using herbicides and insecticides. Therefore, effect of two concentrations (0.1% and 0.2%) of Salvia sclarea L. aqueous extract on lipid peroxidation process, as well as the activity of the antioxidant enzymes (superoxid dismutase, guaiacol peroxidase, pyrogallol peroxidase and catalase) in leaves and roots of pepper (Capsicum annum L.) and black nightshade (Solanum nigrum L.) seedlings were examined. Our results showed that lower concentration of S. sclarea aqueous extract induced lipid peroxidation in black nightshade roots. The second aim was to evaluate effectiveness of aqueous extract as contact toxicant against whitefly (Trialeurodes vaporariorum). It was observed that aqueous extract with concentration of 0.1% showed toxic effect with 56.66% mortality.